Galilean reflections of Milton Friedman's "Methodology of Positive Economics," with thoughts on Vernon Smith's "Economics in the Laboratory" - Schliesser, Eric (2005)
In this article, the author offers a discussion of the evidential role of the Galilean constant in the history of physics. The author argues that measurable constants help theories constrain data. Theories are engines for research, and this helps explain why the Duhem-Quine thesis does not undermine scientific practice. The author connects his argument to discussion of two famous papers in the history of economic methodology, Milton Friedman's "Methodology of Positive Economics," which appealed to example of Galilean Law of Fall in its argument; and Vernon Smith's "Economics in the Laboratory". While the author offers some criticism of Friedman and Smith, most of the article is a friendly reinterpretation of their insights. - Reproduced.
Keywords: Economics